The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.1161/01.cir.56.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic assessment of a normal adult aging population.

Abstract: Echocardiograms were performed on 105 male participants in the National Institutes on Aging's volunteer Longitudinal Study Program. All subjects (25--84 years of age) were physically active and had no evidence of hypertension or cardiovascular disease. Measurements were made of the initial diastolic (E-F) slope of the anterior mitral valve leaflet, the aortic and left ventricular cavity dimensions, and the thickness of the posterior left ventricular wall. Fractional shortening of the minor semi-axis of the lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
235
5
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 535 publications
(264 citation statements)
references
References 37 publications
18
235
5
1
Order By: Relevance
“…On the other hand, de Simone et al have previously reported that increase in LV mass with age in women was associated with hemodynamic and hormonal changes that were not evident in men, suggesting a volume expansion occurring after menopause (31). Furthermore, the LV wall thickness and LV mass have been shown to significantly increase with advancing age in healthy normotensive subjects (32,33). Therefore, a possible explanation for the absence of an association between LV mass and age in our female hypertensive patients would be the small sample size.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, de Simone et al have previously reported that increase in LV mass with age in women was associated with hemodynamic and hormonal changes that were not evident in men, suggesting a volume expansion occurring after menopause (31). Furthermore, the LV wall thickness and LV mass have been shown to significantly increase with advancing age in healthy normotensive subjects (32,33). Therefore, a possible explanation for the absence of an association between LV mass and age in our female hypertensive patients would be the small sample size.…”
Section: Discussionmentioning
confidence: 98%
“…Another risk factor for AF may be the increase in left atrial size that accompanies advancing age in otherwise healthy persons. 33 Limited data available in older subjects without apparent heart disease support a marked age-associated increase in the prevalence and complexity of ventricular ectopy (VE), both at rest and during exercise, at least in men. A steep increase in the prevalence of VE with advancing age occurs in both those clinically free of heart disease and in unselected populations.…”
Section: Heart Rhythmmentioning
confidence: 99%
“…These researchers have reported that age was the major determinant of aortic size among the normal population 17,18) . The Framingham Heart Study reported that the size of the aortic root was determined by age, body weight, height, and sex, and was slightly influenced by blood pressure 19) .…”
Section: Ultrasound Examination Of Aortic Sizementioning
confidence: 99%